Obesity perception survey among youth in Turkey: instrument development and test-retest reliability - PINAR, SALİH (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2019)
Background/aim: We aimed to develop an instrument that can assess the perceptions and opinions of young people regarding the causes and consequences of obesity and the role of individuals, families, communities, and government in addressing obesity. Materials and methods: A 36-question (101-item) survey was developed by adopting, translating, and revising multiple-choice or Likert-scale questions from existing surveys to assure construct cross-cultural validity. A two-factor mixed-effects model estimated the intraclass correlation coefficient (ICC) to measure the test-retest reliability of questions administered 2 weeks apart to a convenient sample of Istanbul high school and university students, aged 15-25 years (n = 122). Results: The mean ICC for university and high school was 0.70 and 0.63, respectively. University students were more consistent in relating the problem to society and public policy preferences. High school students were more consistent in relating the problem and solution to themselves and their immediate environments. Using a 0.5 cutoff for the ICC's lower 95% confidence limit, followed by reevaluation of the question flow, a 19-question (36-item) survey was retained for adolescents and a 26-question (52-item) survey for young adults. Conclusion: While the survey items have moderate to excellent reliability for high school and university students, it can be administered longitudinally to suggest changes to policies and interventions, and after cross-cultural validation, it can be utilized to compare obesity perceptions across different populations.
Keywords: Obesity; perception of problems and solutions; adolescents; young adults; CHILDHOOD OBESITY; PHYSICAL-ACTIVITY; OVERWEIGHT; CONSEQUENCES; WEIGHT; PREVALENCE